Association between serum linezolid concentration and haematological toxic effects: a longitudinal study - Hombal, Prashant R.; Gudadappanavar, Anupama M.; Javali, S. B. (International Surgery Journal, 2017)
Background: Linezolid is a commonly used antibiotic and reported various drug related adverse effects mainly haematological toxicity like thrombocytopenia, leukopenia and anaemia. But a significant association between linezolid plasma concentration and drug related adverse effects are not documented yet. This longitudinal observational study aims to study the incidence of drug related haematological toxicities and its association with serum Linezolid concentration and also evaluate the clinical outcome. Methods: After obtaining informed consent, each patient (18-50years) was given linezolid (600mg/12hourly), and evaluated for haematological (haemoglobin, platelets, WBCs), renal (as serum creatinine), and hepatic (as serum transaminases status), together with an assessment of drug C min values. These evaluations were repeated once a week or in concomitance with the development of an adverse event up to the end of linezolid therapy. The parametric dependent ‘t’ test was applied (p<0.05) and normality of data were performed by Kolmogorov Smirnov test, follows normal distribution. Results: There was significant reduction in platelet count and haemoglobin value seen from baseline till end of treatment (p<0.001) and there was 13% reduction in WBC count in all patients on day 14 when compared to baseline (p<0.001) indicating haematological toxicity according to WHO toxicity grading scale. All the patients (n=8; 26.6%) who developed drug related haematological toxicity also showed comparable increase in plasma linezolid concentration (C min) >10mg/L at the end of 14days. Conclusions: The capability to monitor plasma linezolid concentration (C min; trough value) once a week may lead to a significant improvement in clinical use of the drug both in terms of efficacy and tolerability as the study observed that there is association between linezolid concentration and risk of developing drug related haematological toxicity.